Implementation of Quizwhizzer Application on Social Studies Subjects at SMP Negeri 28 Pontianak City - Kustini Handayani; Saiful Bahri (Research and Innovation in Social Science Education Journal (RISSEJ), 2024)
Basically, education cannot be separated from various elements of the development of the existing era, one of which is the development in terms of information and communication technology. So as to give birth to various innovations that can support the learning process and increase students' interest in what is being learned. Technology certainly affects human life and plays a role in the life of the wider community, especially the role of technology in the field of education. By supporting the learning process and increasing student interest, one of them is by providing interesting learning media. As with the Quizwhizzer app, it's a game-based educational app. The purpose of this study is to determine the planning and implementation of the Quizwhizzer application in social studies subjects at SMP Negeri 28 Pontianak City, and to find out the results of the application of the Quizwhizzer application in social studies subjects at SMP Negeri 28 Pontianak City. To achieve this goal, this research is conducted using qualitative research type with case study type. Data collection procedures are carried out using observation, interview and documentation methods. The results of its application are proven to bring better results, it looks like students are more excited and enthusiastic when using the Quizwhizzer application in social studies subjects.